Augustine in the Footsteps of Moses: On the History of Interpretation and Impact of Exodus 3:14a - Jiří Hoblík (Verbum Vitae)
This article compares the revelation of the divine name to Moses in Exod 3:14 and its counterpart in Augustine’s first vision in his Confessiones. The main aim is to elucidate the continuity and difference in Augustine’s relationship with, and thought regarding, the figure of Moses and the revelation Moses received. Methodologically, it is based on comparing the Hebrew, Greek, and Latin versions of the text, their relationship with the history of thought, and on juxtaposing it with selected relevant passages in Augustine’s work. It proceeds from the change brought about by the Greek text through its reception, with particular reference to Philo of Alexandria. The main part of this article focuses on the Ego sum qui sum as the content of Augustine’s visionary experience and as an object of interpretation in interrelation with the philosophical concept of being; the main finding is that Augustine does not define God, but interprets his self-identification with being as the starting point for Augustine’s own indirect reference to being and to humanity’s relationship with the incomprehensible but repeatedly revelatory God.